An Experimental Study on Coal Fines Migration during Single Phase Water Flow. (14th August 2020) - Han, Wenlong; Wang, Yanbin; Fan, Jingjing; Li, Yong; Wu, Xiang; Yu, Yun
Abstract : Coal fines migration and intrusion in coal fractures affect coalbed methane (CBM) wells performance by reducing reservoir permeability and production continuity. Physical simulations are conducted to investigate the permeability variation under different diameter coal fines intrusion at various flow velocities and confining pressures. The results show that the conductivity of fractures is dramatically reduced and hardly recover to its initial condition after coal fines intrusion. The permeability after coal fines intrusion (Pcfi ) has no direct correlation with the increase of flooding velocity, while decreases with the increase of confining pressures. The fractures can be totally blocked by coal fines, while penetration also happened during the flooding process, causing permeability fluctuation. The permeability loss rates value for 80-120 mesh coal fines intrusion are generally <60% compared with the initial permeability, including the flow velocity of 2, 3, 4, 6, 8, and 10 mL/min with confining pressure of 6 MPa and the confining pressure of 2, 3, 4, 5, and 6 MPa with flow velocity of 3 mL/min. However, under 120+ mesh coal fines condition, the permeability loss rates are higher than 85% under most flow velocities and confining pressures. When coal fines become smaller, the permeability loss rates decrease to be lower than 45%, and part the coal fines are discharged with the water flow. Thus, coal fines proper dischargement can partly maintain the reservoir permeability during coalbed methane production. The results would be useful in understanding coal fines intrusion behaviors and its controlling strategies during CBM drainage.